Silica aerogel composited with both plasmonic nanoparticles and opacifiers for high-efficiency photo-thermal harvest. (15th February 2023) - Wang, Tianmi; Si, Qiaoling; Hu, Yang; Tang, Guihua; Chua, Kian Jon
Abstract: Plasmonic nanoparticles are doped in silica aerogels for high-efficiency photothermal conversion of solar energy in seawater desalination and so on. However, this suffers from remarkable heat loss problem via near-infrared radiation. The present work proposes a novel aerogel composited with both plasmonic nanoparticles and opacifiers. The radiative characteristics of the aerogel composite were numerically investigated by coupling the T-matrix method and Monte Carlo method. The opacifiers promote the extinction characteristics in the infrared wavelength range and reduce the radiative thermal conductivity, while the plasmonic nanoparticles enhance the absorption efficiency in the solar spectrum. Moreover, silica aerogels doped with both silver nanoparticles and indium tin oxide (ITO) particles were prepared and tested. It is found that the optimal radius and volume fraction of ITO particles are 1000 nm and 1% at 300 K, respectively, based on the silica aerogel (particle radius of 5 nm and porosity of 95%) doped with silver plasmonic nanoparticles (particle radius of 10 nm and concentration of 5%). They can achieve an absorption efficiency of 87.65% in the solar spectrum and a low transmittance in the infrared range with reduced heat loss. The present work paves a new way to design full-spectrum absorption aerogels for high-efficiency photothermal conversion. Highlights: A new aerogel composited with opacifiers and plasmonic nanoparticles is prepared. The proposed aerogel composite achieves 87.65% solar absorption efficiency. The low transmittance in the infrared range reduces the radiative heat loss. Optimum diameter and concentration of opacifiers are determined. The enhancement mechanism of solar-thermal conversion is revealed theoretically.